Numerical simulation of creep fracture evolution in fractured rock masses - Na, Zhao; Lixin, Meng; Laigui, Wang; Yibin, Zhang (Frontiers in Earth Science, 2022)
The initiation, expansion, and penetration of microscopic cracks in rock is the macroscopic manifestation of creep. This paper investigates mechanical creep characteristics and fracture evolution processes in rock masses with different fracture angles, lengths, and rock bridge dip angles. Single fractures, dual parallel fractures, and fracture groups are considered. The approach comprises discrete element simulation based on continuum mechanics, utilizing the continuous and discontinuous software, GDEM. Single-fracture rock masses are characterized by a progressive fracture development mode dominated by tensile shear failure. The rate of creep and fracture magnitude both increase according to fracture length. With increasing fracture inclination angle, creep rate and fracture magnitude increase and decrease. The creep rate and degree of rupture are highest for fractures inclined at 30°. The dual-fracture rock mass exhibits both tensile crack failure and compressional shear failure. Creep rates are highest, and rupture effects are most apparent at rock bridge inclination angles of 90°. If the rock bridge is too long or too short, the stable creep stage is prolonged, but the creep acceleration stage intensifies due to interaction between fracture-bounded rock masses. The failure mode, in this case, involves collective failure by tension fractures and compressional shear. Creep rate and fracture magnitude increase with the number of fractures, which accelerates rock mass deformation to a certain extent. However, when the number of fractures reaches a certain threshold, a relatively stable structure may become established, slowing down the creep rate, especially during the creep acceleration stage. This study can provide a theoretical basis and reference for investigating the creep rupture law of rock mass engineering and the prevention and control of fractured rock mass geological disasters.